Terrestrial Isopods (Isopoda: Oniscidea) from the Slovenian Karst - Ferenc Vilisics; Aleš Lapanje (Natura Sloveniae)
Hand sorting was performed in 28 habitats of the Slovenian Karst during 2004. Twenty-three terrestrial isopod species were identified, two of which proved to be new for the Slovenian fauna, namely Trichoniscus matulici and Armadillidium nasatum. Synanthropic and semi-natural sampling sites were chosen for collecting samples. The species Orthometopon dalmatinum, Philoscia affinis, Protracheoniscus politus, Trachelipus ratzeburgii were found to be common in semi natural sites, while Androniscus roseus, Chaetophiloscia cellaria and Armadillidium vulgare appeared frequently in synanthropic habitats. Previous investigations of the terrestrial isopod species distribution in the neighbouring northern Italian area showed higher species diversity than in Slovenian western area close to the Italian borderline. This is the reason why a higher terrestrial isopod species diversity is expected during further sampling experiments in Slovenian territory near the Italian border.